Rhotic Generalization Is More Rapid in Biofeedback Than Motor-Based Treatment for Residual Speech Sound Disorder: Secondary Outcomes of a Randomized Controlled Trial. - Preston, Jonathan L.; Hitchcock, Elaine R.; Leece, Megan C.; Benway, Nina R.; Hill, Jennifer; McAllister, Tara (Journal of Speech, Language & Hearing Research, 2026)
Purpose: This study examined the effects of visual biofeedback and nonbiofeedback motor-based treatment on generalization outcomes following speech therapy for children with residual speech sound disorders Method: A total of 108 children aged 9-15 years with RSSD affecting English /ɹ/ were randomly assigned to receive 19 motor-based treatment sessions, with or without visual biofeedback (divided into visual-acoustic biofeedback). The treatment included practice implement several motor learning principles, with task difficulty adjusted based on the child's performance. Children's /ɹ/ accuracy words before and after treatment was rated as correct or incorrect listeners who were blinded to participant characteristics, treatment and time points. Results: The mixed-effects regression model revealed a statistically interaction between treatment type and time point. Specifically, biofeedback and nonbiofeedback motor-based treatment groups made over time, but the amount of generalization to untreated words was greater in the biofeedback condition than in the motor-based treatment. subanalysis comparing biofeedback types, greater generalization following ultrasound biofeedback than visual-acoustic biofeedback, this effect was strongest at one treatment site. Discussion: This randomized controlled trial found that adding biofeedback motor-based treatment can increase the rate of accurate production